Inequality of Educational Opportunity? Schools as Mediators of the Intergenerational Transmission of Income - Rothstein, Jesse (Journal of Labor Economics, 2019)
Intergenerational income transmission varies across commuting zones (CZs). I investigate whether children’s educational outcomes help to explain this variation. Differences among CZs in the relationship between parental income and children’s human capital explain only one-ninth of the variation in income transmission. A similar share is explained by differences in the return to human capital. One-third reflects earnings differences not mediated by human capital, and 40% reflects differences in marriage patterns. Intergenerational mobility appears to reflect job networks and the structure of local labor and marriage markets more than it does the education system.